2001
DOI: 10.1143/jjap.40.2211
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructions of 6H-SiC(0001) Surfaces Studied by Scanning Tunneling Microscopy and Reflection High-Energy Electron Diffraction

Abstract: We study the level spacing distribution p(s) in the spectrum of random networks. According to our numerical results, the shape of p(s) in the Erdős-Rényi (E-R) random graph is determined by the average degree k and p(s) undergoes a dramatic change when k is varied around the critical point of the percolation transition, k = 1. When k 1, the p(s) is described by the statistics of the Gaussian orthogonal ensemble (GOE), one of the major statistical ensembles in Random Matrix Theory, whereas at k = 1 it follows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
2
12
0
1
Order By: Relevance
“…Figure 4(a) shows a RHEED pattern from the SiC with graphene in the azimuth direction of [1010] before oxygen etching, showing diffraction spots of SiC (1×1), SiC (6 √ 3×6 √ 3) and graphene, as has been observed previously [25,26]. The SiC (6 √ 3×6 √ 3), which indicates the presence of the buffer layer are still observed in the RHEED pattern for the oxygen etched surface (Fig.…”
Section: Resultssupporting
confidence: 66%
“…Figure 4(a) shows a RHEED pattern from the SiC with graphene in the azimuth direction of [1010] before oxygen etching, showing diffraction spots of SiC (1×1), SiC (6 √ 3×6 √ 3) and graphene, as has been observed previously [25,26]. The SiC (6 √ 3×6 √ 3), which indicates the presence of the buffer layer are still observed in the RHEED pattern for the oxygen etched surface (Fig.…”
Section: Resultssupporting
confidence: 66%
“…• with respect to the SiC lattice [3]. Diffraction spots from the graphite lattice remain even after annealed at 1800…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that, on 6H-SiC(0001) Siterminated surfaces, graphite layers or carbon nanotubes with shorter length than that on the C-terminated surfaces are produced depending on sample preparation procedures [10]. Previously, we have found that string-shaped structures consisting of graphite structure are produced along step edges on 6H-SiC(0001) Si-terminated surfaces by annealing in UHV [3]. Recently, Derycke, et al have determined string-shaped structures on 6H-SiC(0001) Siterminated surfaces to be carbon nanotubes produced in the direction parallel to the surfaces [11].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations